Fiqh Siyasah Review of Social Welfare in Padang City: How is it Implemented - Candra, Afrikal; Efendi, Faisal; Majid, Ikhwanuddin Abdul; Nurlaila, Nurlaila (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2024)
This is driven by the ongoing prevalence of social welfare issues in the city of Padang. Among the social welfare issues are the problems of street children, homeless people, beggars, street musicians, and street vendors. Regional regulation number 1 of 2012 has addressed that issue. Among the efforts made in regional regulations are preventive efforts, repressive efforts, and rehabilitation efforts. Has that been implemented to the fullest in the city of Padang, and how is it being applied. This study examines the perspective of Fiqh Siyasah on regional regulation number 1 of 2012 and its implementation in the city of Padang. The author uses field research. The data source consists of the primary source, the Regional Regulation No. 1 of 2012, and the secondary data is derived from a variety of literature related to the discussion in this study. The collected data was then analyzed using a content analysis approach. The results of the implementation of Regional Regulation Number 1 of 2012 are still hindered by several obstacles. Among the challenges faced are: the limited facilities and infrastructure to provide guidance for street children, homeless individuals, beggars, street musicians, and street vendors. There is still minimal allocation of funds from the local government to carry out the construction. The development carried out by the Social Service of Padang City can only address the issue of street children and has not yet been implemented effectively, resulting in many individuals who have been rehabilitated being caught in raids again.